2016
DOI: 10.1111/head.12887
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐ and Age‐Related Differences in the Clinical and Neuroimaging Characteristics of Patients With Spontaneous Intracranial Hypotension: A Records Review

Abstract: spontaneous intracranial hypotension, sex, age, magnetic resonance imaging, thunderclap headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In the SIH group, EBP was performed more frequently in women, consistent with the results published in another study [ 29 ]. Under the influence of estrogen, swelling of the cerebral blood vessels in CSF hypovolemia is likely to be more pronounced in young women, leading to more severe headaches [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the SIH group, EBP was performed more frequently in women, consistent with the results published in another study [ 29 ]. Under the influence of estrogen, swelling of the cerebral blood vessels in CSF hypovolemia is likely to be more pronounced in young women, leading to more severe headaches [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…The nding was in keeping with a study from Japan (n = 40), in which it took longer for men to make the rst consultation. 33 Besides, in the present study, men were less likely to have nausea, vomiting, photophobia, and tinnitus despite similar severities of headache, structural changes in the brain, and spinal CSF leakages. In fact, the overall percentages of patients reporting individual associated symptoms in our study were similar to those reported in the literature, 1,20 although whether there could be sex differences has rarely been looked upon speci cally.…”
Section: Discussionsupporting
confidence: 46%
“…The nding was independent of age and delays in presentation, and was consistent with some prior reports. 5,33,44 In fact, SDH in general is also more common in men than in women. 45,46 A recent study from China reported the male gender appeared to be a risk factor for SDH in univariable but not multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…SIH typically manifests as cerebrospinal fluid (CSF) hypotension and the diagnostic feature includes a postural headache [24]. The etiology of the CSF leakage is not understood completely.…”
Section: Discussionmentioning
confidence: 99%